HEREDITARY DISEASES AND SYNDROMES ACCOMPANIED BY FEBRILE CONVULSIONS: CLINICAL AND GENETIC CHARACTERISTICS AND DIAGNOSTIC PROCEDURES - E. L. Dadali; A. A. Sharkov; I. V. Sharkova; I. V. Kanivets; F. A. Konovalov; I. A. Akimova (Русский журнал детской неврологии)
The authors provide a review of the clinical and genetic characteristics of hereditary diseases and syndromes accompanied by febrile convulsions, which is illustrated by examples of their own observations. The paper sets forth the possibilities and limitations of using current methods for the molecular genetic diagnosis of idiopathic and symptomatic epilepsies. The most effective and less expensive technique of molecular genetic analysis is shown to be an exome sequencing test using the panels of genes responsible for the occurrence of diseases with simi1ar clinical symptoms. The paper also presents the structure of the panel of genes responsible for the occurrence of monogenic epilepsies, which has been designed at the Genomed Clinic and includes 448 genetic variants. It also determines the significance of using a chromosomal microarray analysis to diagnose both chromosomal and monogenic diseases accompanied by convulsions.